EFFECT OF DETONATION SOIL SOFTENING ON CARBONATE AND SULFATE SALTS (Academia Science Repository, 2023)
The article presents the changes in carbonates and sulfates, calcium, magnesium in irrigated arzik-shokh layered meadow saz soils of Central Fergana under the influence of detonation treatment.